Maternal feelings regarding the kangaroo mother care and the neonatal intensive unit care - Luize Harff, Augusta; Groff Vivian, Aline; Anziliero Aross, Guilherme i; Pavin Schumann, Caroline (Seven Editora, 2023)
Objective - To know the perception of mothers of premature babies about Kangaroo Mother Care. Method - Qualitative, descriptive, exploratory study, carried out with mothers of premature infants admitted to a tertiary neonatal ICU at a University Hospital in Southern Brazil. Results - Seven mothers, aged between 19 and 43, participated in semi-structured interviews. Maternal feelings ranged between fear and security about the baby and the joy of skin-to-skin contact. The mothers emphasize the importance of the practice and considered the hospitalization itself, having their children away from home and commuting so that they could be with them as the greatest difficulty. Conclusions - The CM and the kangaroo position are important for mothers and babies, with benefits for both, and it is essential to expand it among health professionals who work with these patients.DOI: https://doi.org/10.56238/devopinterscie-139